Fiscal and Economic Effects of Local Austerity - Melinda Fremerey; Andreas Lichter; Max Löffler (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the consequences of a large-scale austerity program targeting financially-constrained municipalities in Germany. For identification, we exploit the quasi-random assignment of treatment among equally-distressed municipalities using a difference-in-differences design. The policy helped targeted municipalities to consolidate budgets. Whereas the amount of fiscal consolidation was homogeneous among treated municipalities, strategies of consolidation differed between smaller and larger municipalities. The former primarily cut spending on local public services, whereas the latter predominantly relied on tax increases. We detect no adverse economic effects but sizable negative effects on population levels and house prices in municipalities reducing local amenities.
Keywords: H74; H73; H11; H30; 330; austerity; fiscal consolidation; local amenities; taxes; spatial equilibrium